Raising an emotionally healthy child when a parent is sick - Rauch, Paula K. (McGraw-Hill, 2006)
Dr. Rauch is founder and director of the Parenting at a Challenging Time program at Mass General's Psychiatry Department, ranked #1 by U.S. News and World Report The National Cancer Institute reports that one in four cancer patients has children under 18, and millions more children have parents with other serious medical conditions PACT has helped hundreds of parents and trained thousands of health care providers. It has been recognized by the Institute of Medicine; acclaimed by the "Chronicle Show" on Boston's channel 5; and Dr. Rauch received the 2003 Kenneth B. Schwartz Massachusetts Compassionate Caregiver of the Year award